What is the Progress of Multi-cultural Education Implementation in Indonesia: A Critical Recommendation Analysis - Mariske, Edeh Dike (Buletin Edukasi Indonesia, 2025)
Indonesia’s national curriculum embeds the values of Pancasila, promoting unity in diversity as a foundational principle of education. Within the Merdeka Curriculum, these values are further emphasized through the P5 (Projek Penguatan Profil Pelajar Pancasila) co-curricular framework, with themes such as Bhinneka Tunggal Ika (Unity in Diversity) playing a central role. Schools across Indonesia have adopted multicultural education approaches through subject-based learning, particularly in Civic Education, as well as through co-curricular P5 projects and diverse extracurricular activities. However, several key challenges persist, including limited teacher training on multicultural pedagogy, resource constraints, and inconsistencies in implementation across regions. In response, culturally grounded educational programs have begun to emerge, aimed at preserving local wisdom and enhancing students’ cultural understanding in alignment with regional traditions. This paper explores the current practices, opportunities, and challenges of implementing multicultural education in Indonesia, with a focus on the integration of local cultural values within the national curriculum framework.